2006
DOI: 10.1590/s0034-72992006000200006
|View full text |Cite
|
Sign up to set email alerts
|

O uso da acupuntura para alívio imediato do zumbido

Abstract: O zumbido, definido como percepção consciente de um som originado nas orelhas ou no sistema nervoso do paciente, representa até os dias atuais um grande desafio no que concerne seu tratamento, baseia-se na estimulação com agulhas de pontos específicos definidos sobre a anatomia humana. A utilização da Acupuntura (ACP) em sintomas como o zumbido assemelha-se ao modelo aplicado nos quadros álgicos, já que ambos estão relacionados como experiência sensorial e emocional subjetiva e desagradável. OBJETIVO: Estudar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
(2 reference statements)
0
11
0
1
Order By: Relevance
“…Among the numberless etiologies of tinnitus, the otological, metabolic, cardiovascular diseases; cervical column, dental, neurological, psychiatric and other pathologies related to drug ingestion, alcohol and tobaccoism (6,7). Not to mention the reduction in the auditory acuity, exposure to noises, head and cervical lesions, factors of life style and mental status (8).…”
Section: Introductionmentioning
confidence: 99%
“…Among the numberless etiologies of tinnitus, the otological, metabolic, cardiovascular diseases; cervical column, dental, neurological, psychiatric and other pathologies related to drug ingestion, alcohol and tobaccoism (6,7). Not to mention the reduction in the auditory acuity, exposure to noises, head and cervical lesions, factors of life style and mental status (8).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Many acupuncture studies have used subjective data to assess its effect, such as scores to assess symptom improvement. 16,17 Axelsson et al (1994) studied the efficacy of acupuncture in tinnitus patients by using a visual analog scale. This study showed no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Studies tend to use the patient's reference of a subjective sensation to analyze the effect of treatment when dealing with tinnitus. 16,17 A systematic review of the efficacy of acupuncture in the treatment of tinnitus concluded that the belief that acupuncture is effective for treating tinnitus is not based on evidence from controlled, randomized studies. 18 Auditory assessment has progressed and may provide help in evaluating and monitoring tinnitus patients before and after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a symptom that can reflect on the functioning of the organism of an individual as a whole, and can be caused by numerous affections including otological, metabolic, neurological, orthopedic, cardiovascular, pharmacological, odontological, and/or psychological, which, in turn, may be present concomitantly in the same individual. 2,3 Tinnitus consists of a symptom that is present in 15% of the general population, and its incidence increases to 33% in the elderly. 4 Approximately 40% of tinnitus patients also suffer from hyperacusis, which consists of a decreased tolerance to sounds at intensities considered comfortable to most people.…”
Section: Introductionmentioning
confidence: 99%